Cathodic Stripping Determination of Water in Organic Solvents. Issue 3 (2nd February 2014) - Xiao, Changlong; Weremfo, Alexander; Wan, Chenyang; Zhao, Chuan
Abstract A cathodic stripping voltammetry (CSV) method has been developed to determine water content in organic solvents based on electrooxidation of a gold electrode in the presence of water to form gold oxides upon anodic polarizations. Following cathodic potential scan, a sharp reductive stripping peak of gold oxides is generated and the magnitude of the peak current is related to the water content in the organic solvents. The method has been applied for determination of water in four commonly used water miscible organic solvents, acetonitrile, tetrahydrofuran, acetone and glacial acetic acid, with limits of detection of 60, 10, 40 and 10 ppm, respectively.